Dinamika Kenabian Israel dan Timur Dekat Kuno: Pola Inkulturasi dan Diferensiasi - Sunkudon, Pieter G.O.; Laia, Harman Z.; Daud, Daud (JURNAL ILUMINASI, 2025)
The prophetic tradition is not only found in Judaism but also in various Ancient Near Eastern civilizations, such as Egypt, Assyria, Babylon, and Canaan. This study aims to analyze the dynamics of Israelite prophecy in relation to Ancient Near Eastern prophetic traditions by highlighting patterns of inculturation and differentiation. This research employs a historical-comparative approach and theological hermeneutics by examining prophetic texts in the Bible and Ancient Near Eastern sources. The results show that Israelite prophecy shares similarities with Ancient Near Eastern prophecy in terms of revelation methods and the social roles of prophets but differs in its monotheistic theology and focus on social justice. The study concludes that Israelite prophecy functioned not only as a medium for divine revelation but also as an agent of social change. This research contributes to biblical theology, comparative religion, and its relevance to contemporary spiritual and social life.   Authors Biography Pieter G.O. Sunkudon, Sekolah Tinggi Teologi Injili Indonesia PaluScopus ID: 59546443500Google Scholar:  pHG6TXQAAAAJ Harman Ziduhu Laia, Sekolah Tinggi Teologi Injili Indonesia SurabayaScopus ID: 58954546000Google Scholar:  pHG6TXQAAAAJ Daud Daud, Sekolah Tinggi Teologi Injili Indonesia PaluScopus ID: author IDGoogle Scholar:  3A8NWAAAAAJ